2022
DOI: 10.1027/1015-5759/a000665
|View full text |Cite
|
Sign up to set email alerts
|

The Utrecht-Management of Identity Commitments Scale (U-MICS)

Abstract: Abstract. The current study proposed the adaptation of the Utrecht-Management of Identity Commitments Scale (U-MICS) to the religious domain as an instrument to measure both individuals’ religious identity formation processes (when a variable-centered approach is adopted) and religious identity statuses (when a person-centered approach is adopted). The scale has been tested on a sample of 727 Italian participants aged 13–65 years, by collecting evidence of score structure, convergent, and criterion-related val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Somewhat different results were obtained by Piotrowski (2021) using the Meeus-Crocetti model and distinguishing the statuses using cluster analysis. His results largely confirmed observations from other processual studies (Crocetti et al, 2008a;Sorgente et al, 2022) and showed that based on three processes, five different identity statuses in the parenting domain can be distinguished: Achievement (high commitment, high in-depth exploration, low reconsideration of commitment), Foreclosure (high commitment, moderate in-depth exploration, low reconsideration), Moratorium (low commitment, low in-depth exploration, high reconsideration), Diffusion (relatively low intensity of all processes), and Searching Moratorium (low commitment, high in-depth exploration, low reconsideration). Compared to earlier studies by Fadjukoff et al (2016), Piotrowski (2021) observed a significantly higher percentage of parents identifying poorly with their role and experiencing identity uncertainty (Moratorium 15.0% and Diffusion 14.5%).…”
Section: Parental Identity Statusessupporting
confidence: 90%
“…Somewhat different results were obtained by Piotrowski (2021) using the Meeus-Crocetti model and distinguishing the statuses using cluster analysis. His results largely confirmed observations from other processual studies (Crocetti et al, 2008a;Sorgente et al, 2022) and showed that based on three processes, five different identity statuses in the parenting domain can be distinguished: Achievement (high commitment, high in-depth exploration, low reconsideration of commitment), Foreclosure (high commitment, moderate in-depth exploration, low reconsideration), Moratorium (low commitment, low in-depth exploration, high reconsideration), Diffusion (relatively low intensity of all processes), and Searching Moratorium (low commitment, high in-depth exploration, low reconsideration). Compared to earlier studies by Fadjukoff et al (2016), Piotrowski (2021) observed a significantly higher percentage of parents identifying poorly with their role and experiencing identity uncertainty (Moratorium 15.0% and Diffusion 14.5%).…”
Section: Parental Identity Statusessupporting
confidence: 90%
“…This result is partially in line with previous studies finding that religious commitment is positively associated with subjective well-being (Villani et al, 2019). Even if the lack of the effect of religious identity on prosocial orientation leading to the non-significant indirect effect on flourishing appears as inconsistent with other studies showing the association between religiosity and feelings of empathy and compassion (Markstrom et al, 2010), prosociality (Bennett & Einolf, 2017) and altruistic behaviors in young adults (Zarghi & Bolghan-Abadi, 2021), this result should be read with caution because the questionnaire used to measure religious identity does not consider the social dimension of religiosity, such as belonging to the religious community (Sorgente et al, 2022). Also in this case we found that the model works well both for believer and uncertain emerging adults keeping the COVID-19 impact variable under control.…”
Section: Discussionmentioning
confidence: 81%
“…Within the broader construct of religiousness (or religiosity) concerning the public or private adherence to beliefs and rituals of a religion, here we focused on religious identity conceived as the extent to which people self-identify with a faith tradition/community ( Lopez et al, 2011 ). The religious identity formation was measured by the 13-item Utrecht-Management of Identity Commitments Scale (U-MICS; Crocetti et al, 2008 ) recently validated in Italian language within the religious domain ( Sorgente et al, 2022 ). The scale is composed of three subscales, each corresponding to a different identity formation process: the 5-item Commitment subscale indicates the process of strong engagement in a religion; The 5-item In-Depth Exploration subscale refers to the process of active probing own current religious commitment; The 3-item Reconsideration of Commitment subscale pertains to the process of questioning different religious commitment when current religion is no longer fulfilling.…”
Section: Methodsmentioning
confidence: 99%